Income inequality and crime: Consumption channel / Nur Annizah Ishak - Nur Annizah , Ishak (2020)
The general objective of this study is to examine the relationship between income inequality and crime. Many studies have discussed the relationship between inequality and crime. However, all the literature focused on ‘absolute’ measurements, such as income, poverty, Gini index, education, and employment. They neglected the importance of ‘relative concept’ - a missing element of the way economists analyze inequality. This study argues income inequality is visible through conspicuous consumption. Hence this study proposes conspicuous consumption as another possible channel that could explain the relationship between inequality and crime. Specifically, this study comprises of four specific research objectives. The first goal is to examine the relationship between conspicuous consumption and crime among Malaysians. Second, is to measure the relationship between the love of money and crime among Malaysians. Third, is to analyze the role of love of money in mediating conspicuous consumption and crime. The final objective is to propose recommendations for consumption reform of individuals and government to mitigate inequality and crime behavior. A conceptual framework was developed for this study to explain the relationship of three constructs; conspicuous consumption, love of money, and crime. This study adopts Structural Equation Model-Amos (SEM) in investigating the relationship between the three variables. A survey was conducted on public employees in Malaysia to gather the necessary data. The findings suggest three important outcomes. First, a positive relationship between conspicuous consumption and crime where respondents that have higher conspicuous consumption attitude also have higher propensity to commit a crime, particularly through social comparison. Second, there is a positive relationship between the love of money and crime. The survey found they agreed to commit unethical behavior to maximize their profits or utility. Finally, the finding reveals that the love of money significantly mediates the relationship between conspicuous consumption and propensity to crime. All of these findings suggest that conspicuous consumption leads to crime. Consumption is not only important for economic utilization but also to determine one’s status in society. As ‘seeking status’ is universal for society, hence it produces a social comparison. The desire for social conformity, particularly to ‘keep up with the Joneses’ combined with the love of money could induce crime. In summary, this study expands the previous literature by providing a possible explanation of the relationship between income inequality and crime. It contributes to the existing academic research by introducing conspicuous consumption as a result of income inequality. This new variable fills in the research gap by providing additional evidence to the inconclusive relationship between inequality and crime. Some implications and recommendations could be taken into consideration in order to mitigate luxury spending or conspicuous consumption behavior. Among them are to regulate consumption, to impose a tax on luxury goods and prudent spending.